Relación de hierro sérico y hemoglobina como aporte al diagnóstico de anemia en escolares de 8 – 12 años de la unidad educativa simón rodríguez de Licán. - Acosta Mañay, Jessica Karina (2018)
The iron deficit is the nutritional deficiency with higher prevalence and the main cause of anemia worldwide, this research work uses a descriptive, non-experimental and cross-sectional study that aims to determine the ratio of serum iron and hemoglobin as a contribution to diagnosis of anemia in schoolchildren of 8 - 12 years of the Simón Rodríguez from Licán Educational Unit, because anemia is an alteration where the number of erythrocytes is scarce to compensate the physiological needs of the organism; this research is based on the ratio of serum iron and concentration of hemoglobin using methods, techniques and clinical laboratory materials ; when performing these tests it is established that not always the relationship of the serum iron values with the values of the hemoglobin concentration help the presumptive diagnosis of anemia since this last determination can vary according to the sex, geographical altitude and age of the person; According to the results obtained in the research, 14 cases were presented in both genders, indicating 9%, establishing in this way that the prevalence of anemia lies in the female gender with 11 cases referring to 7% and in the masculine gender there are 3 cases describing 2% respectively in the population of schoolchildren under study; The purpose of this research work is to prevent the increase in the prevalence of this pathology.